Japanese notebooks : a journey to the empire of signs - Igort, 1958- (Chronicle Books, 2017)
Japan is a place of special fascination for the acclaimed international comics creator Igort, who has visited and lived there more than 20 times, and worked in the country's manga industry for more than a decade. In this masterful new book--part graphic memoir, part cultural meditation--Igort vividly recounts his personal experiences in Japan, creating comics amid the activities of everyday life, and finding inspiration everywhere: in nature, history, custom, art, and encounters with creators including animation visionary Hayao Miyazaki. With beautifully illustrated reflections on subjects from printmaking to Zen Buddhism, imperial history to the samurai code, Japanese film, literature, and manga, this is a richly rewarding book for anyone interested in Japan or comic arts practiced at the highest level.